ANALISIS PENILAIAN TINGKAT KESEHATAN BANK DENGAN METODE RISK BASED BANK RATING - Prima, Argo Putra; Efriyenty, Dian; Azmiana, Risca; Mulawarman (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2024)
The purpose of this research is to assess the level of bank health at Persero Conventional Commercial Banks in an effort to maintain the loyalty and trust of customers and the public. Financial institutions function as institutions that collect funds from the community and reuse them for the community, so that community participation can be increased and ultimately the nation's independence in development can be realized. This research uses the Risk Based Bank Rating method which consists of assessments, namely Risk Profile, Earnings and Capital to assess the health level of Persero Conventional Commercial Banks registered with Bank Indonesia for the period 2017 – 2021. Data collection techniques used by the author to obtain secondary data. Data relating to the research object was obtained from the official Bank Indonesia website. The results of this research show that the Risk Profile Conditions for credit risk and liquidity risk for banks that have received the title of less than healthy and quite healthy, banks should be careful in terms of lending. The condition of profitability at Bank Negara Indonesia, Bank Rakyat Indonesia, Bank Tabungan Negara and Bank Mandiri, which have a bank health level of composite rank one with the description of being very healthy, needs to be maintained. The overall capital condition received the title of very healthy.